1996
DOI: 10.1063/1.117299
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pulsed laser deposition and thermal deposition: Improved layer-by-layer growth of Fe/Cu(111)

Abstract: In the search for a correlation between the magnetism and the microstructure of ultrathin films, straightforward layer-by-layer growth is desirable. The thermal deposition of Fe onto Cu(111), however, does not result in this growth mode. In this letter, we compare the initial growth of Fe on Cu(111) prepared by pulsed laser deposition (PLD) with thermally deposited Fe/Cu(111) using scanning tunneling microscopy (STM). In PLD, from the beginning there is two-dimensional nucleation and growth, in contrast to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…They found that for all coverage up to the maximum coverage max ϭ1 in their simulation, the island density is an increasing function of the intensity I. Defining the quantity M (I,)ϵN(I,)/N(I, max ) they found that the logarithm of M (I,) obeyed very well the scaling form log͓M(I,)͔/log(I)ϭg͓log()/log(I)͔, where the scaling function g(z) was very well approximated by a simple parabola g(z)ϭaz 2 , with a as a constant. Since the irreversible model of Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that for all coverage up to the maximum coverage max ϭ1 in their simulation, the island density is an increasing function of the intensity I. Defining the quantity M (I,)ϵN(I,)/N(I, max ) they found that the logarithm of M (I,) obeyed very well the scaling form log͓M(I,)͔/log(I)ϭg͓log()/log(I)͔, where the scaling function g(z) was very well approximated by a simple parabola g(z)ϭaz 2 , with a as a constant. Since the irreversible model of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is a technique that may improve layer-by-layer growth, 2,3 and is especially suited for the growth of complex multicomponent thin films, e.g., high-temperature superconductors, 4 biomaterials, 5 or ferroelectric films. 6 A great advantage of PLD is the conservation of the stoichiometry of virtually any target material in the deposition.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of standard equipment associated with MBE, including load-locking, UHV with a base pressure of 7x10 11 Torr, 5-axis sample manipulator, backside tungsten filament heating as well as water-cooled stage. Molecular beam epitaxy is provided by solid source effusion cell, while a quartz window and laser ablation rotating-target system are added to provide pulsed-laser deposition capabilities.…”
Section: Methodsmentioning
confidence: 99%
“…Additional rate equation models for pulsed and energetic flux are also being developed [10], which suggest additional effects relating to instantaneous flux and frequency dependence of pulses. Experimental studies [5,11] of epitaxy via PLD typically demonstrate smoother films, a lower kinetic roughening temperature, and increased critical epitaxial thickness. However these are typically not under ultrahigh-vacuum (UHV) conditions, and compared only to MBE results in the literature (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter the growth behavior of PLD under the influence of EhrlichSchwoebel barriers will be discussed. The aim of this work is to give an insight into possible reasons why in some experimental situations PLD has been shown to produce better layer-by-layer growth than ordinary molecular beam epitaxy (MBE) [Jenniches et al (1996)]. …”
Section: Introductionmentioning
confidence: 99%